Strategi Membangun Reputasi Karier Sebagai Pengusaha Salon Melalui Personal Branding Bagi Anggota Tiara Kusuma Kota Semarang - Sofia Daniati; Argiska Oca Sugiyanto; Amalia Dika Brilianti; Aulia Romadona (ABDI KARYA : Pengabdian Kepada Masyarakat, 2025)
Salon entrepreneurship can be a promising profession if supported by good personal branding. A salon entrepreneur must have a characteristic that differentiates them from others in terms of appearance, communication style or expertise. Personal branding can support career reputation if the application is good, if personal branding is applied poorly it will form a bad image in the community. Therefore, the purpose of carrying out community service activities at Tiara Kusuma DPC Members in Semarang City is to provide understanding to the participants so that they can apply personal branding to themselves so that they have a better self-image and can support the sustainability of the salon business they are working on. This service activity begins by analyzing the needs of the participants and then compiling the material presented according to the results of the analysis. Furthermore, the implementation of activities is to deliver some material related to the understanding of personal branding, the purpose of personal branding and how to create personal branding to improve career reputation as a salon entrepreneur. After the material is delivered, it is continued with a joint discussion and evaluation through questions and answers related to the material presented. The enthusiasm of the training participants can be seen from the many questions asked related to the problems and obstacles experienced so that they can become material for discussion.